Ocena przedsiębiorstwa dłużnika przez tymczasowego nadzorcę sądowego - Gurgul, Stanisław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The new bankruptcy and reorganisation law, currently applied in Poland, has brought in a new institution of Temporary Court Supervisor. His duty is to determine the economic situation of debtor's enterprise at the time of insolvency applying, so on this base is the insolvency court can decide whether to open insolvency procedure to the debtor's enterprise or to reject the application. This may be the moment to decide if it is possible to conclude an arrangement with the creditors, whether the enterprise has an insolvency ability and, in case of liquidation insolvency, in which degree the creditors demands could be satisfied. This institution can't be fully advantaged yet, because of a lack of knowledge and education of syndics, who should be better trained and chosen to practice this occupation. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 85-95